Biomarkers could facilitate prediction of worse clinical outcome of cancer with special insight to cervical cancer - Czerniak, Bartosz; Olszewska-Słonina, Dorota (Contemporary Oncology/Współczesna Onkologia, 2018)
Cervical cancer incidence, globally, is second only to malignant breast cancer. The main causative factor is thought to be human papillomavirus (HPV) infection as a result of many sexual partners. Despite radiotherapy, chemotherapy and surgical treatment, the survival rate of patients with advanced disease is low. Metastasis is one of the stages of cancerogenesis in which tumour cells acquire the ability to migrate and create tumour secondary foci. Tumour biomarkers, proteins produced by neoplastic cells, quantified in body fluids or in tissues, play a key role in treatment monitoring and in determining the prognosis for further years of life. In recent years, the search for cervical cancer biomarkers has been intensively sought. They can become a decisive factor in making radical treatment and, in the near future, a potential therapeutic goal. The article presents and briefly describes the biomarkers of metastasis in cervical cancer studied in recent years and highlights their potential therapeutic use.